Cross-reactivity between antibodies induced by European swine influenza vaccines and Spanish swine influenza strains - Encinas, Paloma; Nogales, Aitor; Nelson, Martha I.; García-Sastre, Adolfo; del Real, Gustavo (Frontiers in Veterinary Science, 2026)
BackgroundVaccination is an essential tool for controlling the severity of influenza in swine and its spillover risk to humans. Due to fast mutation rates, genomic reassortment, and the high antigenic variability of influenza A viruses (IAV), it is necessary to update vaccine strains to better match and neutralize circulating viruses.MethodsIn this study, we analyzed the immune cross-reactivity of hemagglutination inhibition (HI) antibodies induced by currently approved European swine influenza vaccines against Spanish swine influenza viruses (SIVs) isolated from 2016 to 2021, as well as human IAV strains, using a murine model. Sera from immunized mice with monovalent (MVV) or trivalent (TVV) swine influenza vaccines were tested against Spanish representative SIVs carrying HAs from different subtypes and lineages using a HI serological assay. Amino acids in the antigenic motifs of the receptor binding site (RBS) of the IAV HA were compared and contrasted among SIV strains to detect changes that may affect protein antigenicity.ResultsSera from mice immunized with MVV or TVV showed no HI antibodies against a 2019 Eurasian avian-like H1 (EAswH1) SIV. TVV did not induce cross-reactive HI antibodies against two human seasonal H3 SIV from the 2000s (2000s-like H3) or against the human seasonal H3 vaccine strain (HuVacH3). Geometric mean (GM) HI titers of sera from TVV-immunized mice were below the protection threshold (GM < 40) against the recent human seasonal-like H1 (HUswH1) SIV, against an EAswH1 SIV, and against the human seasonal H1 vaccine strain (HuVacH1). HI antibodies induced by MVV showed high cross-reactivity with a 2019 EAswH1 SIV isolate.ConclusionCurrently authorized vaccines do not induce HI antibodies against some contemporary SIV circulating in Spain, nor against human seasonal influenza vaccine strains. Updating vaccine strains to better match new SIVs emerging in Spanish swine is warranted.